Utility of copeptin in acute myocardial infarction - Samsudin, Intan Nureslyna; Darul Ridzuan, Ilyas Syafiq; Chellappah Thambiah, Subashini; Hasan, Md. Shariful (Community Health Society Malaysia, 2015)
Copeptin, a surrogate marker for vasopressin, is increased immediately following an acute myocardial infarction (AMI). In several studies, using a single multi-marker strategy, copeptin in combination with either conventional or high-sensitive troponin drawn at presentation of patients with AMI was able to rule out AMI with high negative predictive value (NPV). Copeptin is also reviewed as a prognostic marker for predicting mortality and morbidity in AMI and allows risk stratification of patients into low, moderate and high risk patients. This review looked at past researches conducted on copeptin as either a diagnostic marker for those presenting to emergency department with chest pain, or its prognostic value.